Evaluation of the 'Jumping to conclusions' bias in different subgroups of the at-risk mental state: from cognitive basic symptoms to UHR criteria. Issue 10 (20th April 2016) - Rausch, F.; Eisenacher, S.; Elkin, H.; Englisch, S.; Kayser, S.; Striepens, N.; Lautenschlager, M.; Heinz, A.; Gudlowski, Y.; Janssen, B.; Gaebel, W.; Michel, T. M.; et al.
Abstract : Background: Patients with psychosis display the so-called 'Jumping to Conclusions' bias (JTC) – a tendency for hasty decision-making in probabilistic reasoning tasks. So far, only a few studies have evaluated the JTC bias in 'at-risk mental state' (ARMS) patients, specifically in ARMS samples fulfilling 'ultra-high risk' (UHR) criteria, thus not allowing for comparisons between different ARMS subgroups. Method: In the framework of the PREVENT (secondary prevention of schizophrenia) study, a JTC task was applied to 188 patients either fulfilling UHR criteria or presenting with cognitive basic symptoms (BS). Similar data were available for 30 healthy control participants matched for age, gender, education and premorbid verbal intelligence. ARMS patients were identified by the Structured Interview for Prodromal Symptoms (SIPS) and the Schizophrenia Proneness Instrument – Adult Version (SPI-A). Results: The mean number of draws to decision (DTD) significantly differed between ARM -subgroups: UHR patients made significantly less draws to make a decision than ARMS patients with only cognitive BS. Furthermore, UHR patients tended to fulfil behavioural criteria for JTC more often than BS patients. In a secondary analysis, ARMS patients were much hastier in their decision-making than controls. In patients, DTD was moderately associated with positive and negative symptoms as well as disorganization and excitement. Conclusions: Our data indicate an enhanced JTC bias in the UHR group compared to ARMS patients with only cognitive BS. This underscores the importance of reasoning deficits within cognitive theories of the developing psychosis. Interactions with the liability to psychotic transitions and therapeutic interventions should be unravelled in longitudinal studies.